Transvenous and non-transvenous implantable cardioverter-defibrillators in children, adolescents, and adults with congenital heart disease: who is at risk for appropriate and inappropriate shocks?. Issue 1 (17th October 2018) - Krause, Ulrich; Müller, Matthias J; Wilberg, Yannic; Pietzka, Matthias; Backhoff, David; Ruschewski, Wolfgang; Paul, Thomas
Abstract: Aims: Non-transvenous implantable cardioverter-defibrillators (ICDs) as used in small patients and in patients with congenital heart disease (CHD) have not been compared with transvenous systems with respect to safety and efficacy yet. Aim of the present study was to describe the prevalence of and to identify contributing factors for appropriate and inappropriate ICD discharges in patients with non-transvenous and transvenous ICD. Methods and results: Single centre analysis of all paediatric and CHD patients who had received an ICD since 1995. One hundred and ninety-five patients were included. A transvenous system had been implanted in 153 (78%) subjects, the remaining 42 (22%) individuals received an extracardiac (EC)-ICD system. During mean follow-up of 4.5 years appropriate ICD shocks were noted in 32 (16%) individuals, whereas inappropriate shocks occurred in 22 (11%) patients. Appropriate shocks were more frequent in patients with an EC-ICD than in individuals with transvenous systems (29% vs. 13%, P  = 0.02). Rapidly conducted atrial tachycardia (AT) was the most common reason for inappropriate shocks (76%). Rate of inappropriate shocks was not different between EC and transvenous systems (12% vs. 11%, P  = 0.26). Lead failure was more prevalent in subjects with an EC-ICD (29% vs. 7%, P  = 0.001). Conclusion: Individuals with EC-ICD systems were particularly prone to experience appropriate shocks. As rapidly conducted AT was the most common reason for inappropriate ICD shocks, rigorous treatment of these arrhythmias and proper ICD programming are mandatory. Though lead failure was of concern in EC-ICD patients, EC-ICD systems were not inferior with respect to inappropriate shocks.